Optimizing Students' Learning Interest In Fiqih Subjects Using Ice Breaking Techniques At Muhammadiyah 47 Sunggal Junior High School - Riska Khadijah; Selamat Pohan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to optimize students' interest in the subject of Fiqih through the implementation of ice breaking techniques at SMP Muhammadiyah 47 Sunggal. A qualitative approach with descriptive method was employed in this study. Data were obtained through interviews with Fiqih teachers and students of class VII-A at SMP Muhammadiyah 47 Sunggal, as well as classroom observations. The results of the research show that Fiqih teachers have used various ice breaking methods, such as performances and games, to enhance students' interest in the subject of Fiqih. Ice breaking is effective in boosting students' enthusiasm and concentration, and it has a positive impact on motivation, engagement, understanding, and interest in learning among students. However, the main challenge often encountered is the lack of enthusiasm among some students in participating in ice breaking activities. Nevertheless, this does not affect other students who remain enthusiastic. Therefore, teachers need to create more creative and engaging ice breaking methods to increase overall student enthusiasm. Thus, this research contributes to understanding the importance of implementing ice breaking to enhance students' interest in the subject of Fiqih at SMP Muhammadiyah 47 Sunggal.